1989
DOI: 10.1161/01.str.20.11.1531
|View full text |Cite
|
Sign up to set email alerts
|

Nimodipine attenuates both increase in cytosolic free calcium and histologic damage following focal cerebral ischemia and reperfusion in cats.

Abstract: To clarify the mechanism of its effect on ischemic stroke, we investigated the effect of nimodipine, a dihydropyridine calcium antagonist, on changes in cytosolic free calcium, cortical blood flow, and histologic changes following focal cerebral ischemia and reperfusion in 14 cats. Using indo-1, a fluorescent intracellular Ca 2+ indicator, we simultaneously measured changes in the Ca 2+ signal ratio (400 506 nm), reduced nicotinamide adenine dinucleotide fluorescence (464 nm), and reflectance (340 nm) during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(45 citation statements)
references
References 45 publications
3
42
0
Order By: Relevance
“…These concentrations of glutamate antagonists fully blocked excitatory postsynaptic potentials (EPSPs) evoked by the activation of glutamatergic corticostriatal fibers in brain slice preparations ( Figure 3C). 11,20 Blockers of high voltage-activated Ca 2ϩ channels have been reported to reduce the neuronal vulnerability to ischemia 27 and the ischemic depolarization in cortical neurons. 2 Thus, we also studied the effect of preincubation of the slices in 10 mol/L nifedipine on the ischemic depolarization.…”
Section: Antagonists Of Glutamate Receptors and Neuroprotective Drugsmentioning
confidence: 99%
“…These concentrations of glutamate antagonists fully blocked excitatory postsynaptic potentials (EPSPs) evoked by the activation of glutamatergic corticostriatal fibers in brain slice preparations ( Figure 3C). 11,20 Blockers of high voltage-activated Ca 2ϩ channels have been reported to reduce the neuronal vulnerability to ischemia 27 and the ischemic depolarization in cortical neurons. 2 Thus, we also studied the effect of preincubation of the slices in 10 mol/L nifedipine on the ischemic depolarization.…”
Section: Antagonists Of Glutamate Receptors and Neuroprotective Drugsmentioning
confidence: 99%
“…Most studies on the role of excessive Ca 2ϩ influx in cell death have focused on Ca 2ϩ entry via ligand-gated channels (Rothman and Olney, 1987;Choi, 1988); however, it is becoming increasingly recognized that VGCCs, particularly of the L-type, can be a route for toxic levels of Ca 2ϩ influx after a number of insults (Scriabine et al, 1989;Uematsu et al, 1989;Lobner and Lipton, 1993;Lipton, 1994;Stuiver et al, 1996). Furthermore, VGCCs represent a major Ca 2ϩ entry pathway even during the physiological activation of ligand-gated Ca 2ϩ channels (Miyakawa et al, 1992;Jaffe et al, 1994;Regehr and Tank, 1994;Stuart and Sakmann, 1994;Magee and Johnston, 1995;Yuste and Denk, 1995).…”
Section: Abstract: Hippocampal Neurons; Calcium Currents; Cell Deathmentioning
confidence: 99%
“…For instance, one could test the hypoth-esis that a calcium channel blocker, such as nimodipine, changes the slope or magnitude of the early dopamine release and perhaps even attenuates the reperfusion response. In fact, Uematsu et al 32 have already shown that nimodipine attenuates both increase in cytosolic free calcium and histological damage following focal cerebral ischemia and reperfusion in cats. Further studies to understand and modify this reperfusion phenomenon are warranted.…”
mentioning
confidence: 98%